Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the expression \((2 - 5i)(p + q)(i)\) given that \( p = 2 \) and \( q = 5i \), follow these steps:
1. Substitute the values for \( p \) and \( q \):
Given:
[tex]\[ p = 2 \][/tex]
[tex]\[ q = 5i \][/tex]
2. Form the second term:
Substitute \( p \) and \( q \) into \( p + q \):
[tex]\[ p + q = 2 + 5i \][/tex]
3. Multiply the first term by the second term:
The expression becomes:
[tex]\[ (2 - 5i)(2 + 5i) \][/tex]
To expand the product, use the distributive property (FOIL method):
[tex]\[ (2 - 5i)(2 + 5i) = 2 \cdot 2 + 2 \cdot 5i - 5i \cdot 2 - 5i \cdot 5i \][/tex]
[tex]\[ = 4 + 10i - 10i - 25i^2 \][/tex]
Note that \( i^2 = -1 \):
[tex]\[ = 4 + 10i - 10i - 25(-1) \][/tex]
[tex]\[ = 4 + 25 \][/tex]
[tex]\[ = 29 \][/tex]
4. Multiply the result by \( i \):
Now, take the result \( 29 \) and multiply it by \( i \):
[tex]\[ 29 \cdot i = 29i \][/tex]
Therefore, the evaluated expression \((2 - 5i)(2 + 5i)(i)\) is:
[tex]\[ \boxed{29i} \][/tex]
This matches the true result described in the problem.
1. Substitute the values for \( p \) and \( q \):
Given:
[tex]\[ p = 2 \][/tex]
[tex]\[ q = 5i \][/tex]
2. Form the second term:
Substitute \( p \) and \( q \) into \( p + q \):
[tex]\[ p + q = 2 + 5i \][/tex]
3. Multiply the first term by the second term:
The expression becomes:
[tex]\[ (2 - 5i)(2 + 5i) \][/tex]
To expand the product, use the distributive property (FOIL method):
[tex]\[ (2 - 5i)(2 + 5i) = 2 \cdot 2 + 2 \cdot 5i - 5i \cdot 2 - 5i \cdot 5i \][/tex]
[tex]\[ = 4 + 10i - 10i - 25i^2 \][/tex]
Note that \( i^2 = -1 \):
[tex]\[ = 4 + 10i - 10i - 25(-1) \][/tex]
[tex]\[ = 4 + 25 \][/tex]
[tex]\[ = 29 \][/tex]
4. Multiply the result by \( i \):
Now, take the result \( 29 \) and multiply it by \( i \):
[tex]\[ 29 \cdot i = 29i \][/tex]
Therefore, the evaluated expression \((2 - 5i)(2 + 5i)(i)\) is:
[tex]\[ \boxed{29i} \][/tex]
This matches the true result described in the problem.
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.